Internet searching and stock price crash risk: Evidence from a quasi-natural experiment - Xu, Yongxin; Xuan, Yuhao; Zheng, Gaoping (Journal of Financial Economics, 2021)
In 2010, Google unexpectedly withdrew its searching business from China, reducing investors’ ability to find information online. The stock price crash risk for firms searched for more via Google before its withdrawal subsequently increases by 19%, suggesting that Internet searching facilitates investors’ information processing. The sensitivity of stock returns to negative Internet posts also rises by 36%. The increase in crash risk is more pronounced when firms are more likely to hide adverse information and when information intermediaries are less effective in assisting investors’ information processing. In addition, liquidity (price delay) decreases (increases) after Google's withdrawal.